GLOSS TO THE JUDGMENT OF THE COURT OF JUSTICE OF THE EUROPEAN UNION OF 16.11.2016 IN CASE C-301/15 - Dąborowski, Marcin (Człowiek w cyberprzestrzeni, 2020)
The gloss concerns the judgment of the Court of Justice of the European Union of 16.11.16 2016 in case C-301/15, which ruled that Articles 2(a) and 3(1) of Directive 2001/29/EC of the European Parliament and of the Council of 22 May 2001 on the harmonisation of certain aspects of copyright and related rights in the information society must be interpreted as precluding national legislation which entrust an organisation authorised to collect and distribute copyright revenue with the exercise of the right to authorise the reproduction and public digitalisation of 'out-of-commerce' books which are no longer commercially distributed or published in printed or digital form, even though it also allows the authors of or rightholders to those books to object to the said exercise.